Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.mri.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance diffusion-weighted imaging: quantitative evaluation of age-related changes in healthy liver parenchyma

Abstract: The purpose of this study was to verify in healthy liver parenchyma the possible influence of age on DwI-related parameters: apparent diffusion coefficient (ADC), perfusion fraction (PF), diffusion and pseudodiffusion coefficient (D and D ⁎ ). Forty healthy adult volunteers (age range 26-86 years), divided into four age groups, were prospectively submitted to a breath-hold magnetic resonance diffusion imaging (MR-DwI) (two b values, 0-300 and 0-1000 s/mm 2 ). A smaller cohort of 16 subjects underwent a free-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, Pasquinelli et al showed no significant variations in liver DWI quantitative parameters according to the age of the subject [45]. Therefore, we assumed that the possible effects of age in our cohort are far smaller than the demonstrated significant region dependency of the ADC in the liver.…”
Section: Discussionmentioning
confidence: 68%
“…However, Pasquinelli et al showed no significant variations in liver DWI quantitative parameters according to the age of the subject [45]. Therefore, we assumed that the possible effects of age in our cohort are far smaller than the demonstrated significant region dependency of the ADC in the liver.…”
Section: Discussionmentioning
confidence: 68%
“…Second, the average age of the cirrhotic liver group was significantly higher than that of the normal liver group. However, Pasquinelli et al have reported that there are no significant differences in each derived parameter from DWI ( ADC , PF , D *, and D ) between younger and older subjects on healthy parenchyma. Therefore, it is believed that the results derived from our analyses did not depend on age in this research.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, recent literature reports have shown that ADC is not satisfactory for differentiating different solid focal liver lesions or grading fibrosis. On the contrary, the results of the studies devoted to the evaluation and follow‐up of the response of metastatic liver tumors to chemotherapy are encouraging (37). An enormous variability has also been observed among acquisition protocols, image postprocessing, and ADC measurements, leading to an increased number of joint initiatives for standardization protocols (38).…”
Section: Discussionmentioning
confidence: 99%